Egg Freshness Indexes Correlations with Ovomucin Concentration during Storage. (31st December 2022) - Jiang, Yajun; Fu, Dandan; Ma, Ming
Abstract : The relationship between protein changes and egg quality during storage is a critical area of investigation in both basic science and egg product preservation. Viscosity changes in albumen are a sensitive sign of the deterioration process. Ovomucin, which is present in albumen, plays an important role in the gelation of the albumen. Egg freshness indices and ovomucin concentration will alter in response to storage time. This paper analyzed the correlation and gray relational degree between the Haugh unit (HU), yolk index, albumen pH, and ovomucin concentration. We studied the differences in the ovomucin concentration at different levels of HU, yolk index, and pH during storage. We established an equivalent egg age prediction model using ovomucin concentration as the independent variable. The findings indicated a correlation between the freshness indices and the ovomucin concentration. There was a good, significantly positive relationship between HU and ovomucin concentration ( r = 0.713, P < 0.01 ), a positive correlation between the yolk index and ovomucin concentration ( r = 0.699, P < 0.01 ), and a negative correlation between albumen pH and ovomucin concentration ( r = −0.683, P < 0.01 ). The highest Pearson correlation coefficient ( r = 0.970, P < 0.01 ) was obtained between the albumen and ovomucin concentration. Significant differences in ovomucin concentration were observed when HU, yolk index, and pH were varied. The gray relational degree between each freshness parameter and ovomucin concentration was greater than 0.8. Between the HU and ovomucin concentration, there was a gray correlation degree of 0.885, indicating that the HU was the primary factor affecting ovomucin concentration variation during storage. During storage, at 22°C, the ovomucin concentration in albumen was significantly and negatively related to storage time ( r = −0.926, P < 0.05 ). The coefficient of determination for the equivalent egg age prediction model with ovomucin concentration as the independent variable was 0.985 (P < 0.05 ), indicating strong reliability. The study's findings show the possibility of nondestructive prediction of an egg's internal microscopic protein composition using its freshness index value.